Research on the Distribution Rule of Percussion Response Pulse Width in Coin-Tap Test. (29th August 2021) - Li, Jian; Xu, Liping; Yu, Xiaowen; Peng, Jianjun; Huang, Lei
Abstract : The coin-tap method performs nondestructive testing by measuring the width of the tapping response pulse on the surface of the material. Existing studies have shown that defects in the material will cause the width of the tapping response pulse to increase. However, experiments have confirmed that different detection positions in the defective area will show different values of the width of the tapping response pulse, and the physical laws behind it have not been studied yet. To discuss its physical meaning, a mathematical model of the defective area is established, a method for calculating the width of the tapping response pulse is proposed, and a composite honeycomb structure with preset defects is used for data testing. Both the test results and the calculation results show that the pulse width of the tapping response will decrease with the increase of the defect depth and the deviation of the tapping position from the defect center. The consistency between the calculated results and the experimental results shows that the established defect model and pulse width calculation method can better explain the distribution law of the pulse width of the tapping response in the defective area.